Influence of antiviral therapy in the long‐term outcome of recurrent hepatitis C virus infection following liver transplantation. Issue 4 (3rd June 2013) - García‐Reyne, A.; Lumbreras, C.; Fernández, I.; Colina, F.; Abradelo, M.; Magan, P.; San‐Juan, R.; Manrique, A.; López‐Medrano, F.; Fuertes, A.; Lizasoain, M.; Moreno, E.; et al.
Abstract Introduction Severity of recurrent hepatitis C virus (HCV) infection in liver transplant recipients (LTR) is variable and the influence of different factors, including the administration of antiviral therapy in the long‐term outcome is controversial. Methods We analyzed the outcome of a cohort of HCV‐infected LTR who were transplanted in our institution. Patients were divided into 2 groups (severe and non‐severe HCV disease) depending on the presence of a fibrosis score of F ≥2 in the Scheuer index and/or fibrosing cholestasic hepatitis (FCH) in a graft biopsy. Risk factors were studied using logistic regression analysis. Survival of patients was estimated using Kaplan–Meier plots. A total of 146 patients were followed for a mean of 58 months. Results Fifty‐six (34%) patients developed severe HCV disease and showed shorter survival (P < 0.024). Donor age (odds ratio [OR]: 1.04; 95% confidence interval [CI]: 1.02–1.06) and pre‐transplant viral load (VL) >106 UI/mL (OR: 3.5; 95% CI: 1.42–10.61) were the only factors associated with severe HCV infection. Over‐immunosuppression (OR: 2.3; 95% CI: 1.2–4.41) was specifically associated with the development of FCH. Overall, patient survival in recipients who received a full course of anti‐HCV therapy was higher than in patients who did not complete antiviral therapy (P = 0.004) or received no treatment (P = 0.007). Patients with non‐severe HCV infection have a higher probability of receiving a full course of antiviral therapy (P = 0.033). Conclusion In conclusion, donor age, pre‐transplant VL, and over‐immunosuppression were associated with the long‐term development of severe HCV recurrence in liver grafts. Administration of a full course of antiviral therapy was associated with better survival.